(untitled) (Scientific journal of the Fergana State University, 2025)
This article describes today’s digital age, social media life in it, online communication, people’s use of language in social life. It discusses the changing role of digital spaces in shaping individual identities and how language serves as a vehicle for expressing personal values, beliefs, and cultural origins. The article also highlights the emergence of new linguistic forms such as emojis, memes and internet slang and their importance in enabling creative and sensitive online communication.